The Role of Government Tourism Authority in Managing Tourism Development at Malang Regency - Yuniati, Nining; Setyanto, Tri Joko (CV. Ulil Albab Corp, 2025)
The development of regional tourism in Indonesia is still generally the responsibility of local governments. This research aims to determine the role of the Tourism Office in developing tourism in Malang Regency, East Java. The method used is in-depth interviews conducted directly with the Tourism Office. The result is that the government does indeed play an active role and is the dominant actor in the development of regional tourism. This role is carried out by 1) Establish the regional tourism development master plan (RIPPDA) as a guide for tourism development in the next 5 years, 2) Create a tourism branding program, 3) Holding a number of events throughout the year to promote tourism potential, 4) Forming enthusiastic tourism communities down to the village and sub-district levels, 5) Establishing cooperation with private parties, and 6) Formation of District Tourism Partner, 7) Establish masterplan for Tourism Develipment of The District